(untitled) (Research, Society and Development, 2023)
The present study aimed to analyze the hospitalization rate in children under one year of age with bronchitis and acute bronchiolitis, in addition to correlating with the associated lethality rate, comparing the different Brazilian regions rates, between 2013 and 2022. This is an epidemiological, descriptive, longitudinal and retrospective study, with a historical series, conducted through data collection by the TabNet platform of the Department of Informatics of the Unified Health System (DATASUS) about children under one year of age living in Brazil, hospitalized for bronchitis and acute bronchiolitis, between 2013 and 2022 and the associated lethality rate. The data obtained were tabulated in Excel and, then, they were statistically analyzed in the BioEstat 5.3 program, using the Mann-Whitney test and the Spearman correlation test. The South region stood out with the highest hospitalization rate in the country (1,85% e 2,98%), followed by Southeast (1,34% a 2,41%), Midwest (0,73% a 1,98%), North (0,55% a 1,15%) e Northeast (0,53% a 0,99%). On the other hand, the North stands out as the region with the highest lethality rate (0,19%-0,74%), followed by Northeast (0,09%-0,41%), Southeast (0,12%-0,31%), Midwest (0,09%-29%) e South (0,09%-0,17%). It is concluded that the North and Northeast regions have the lowest hospitalization rates and highest lethality rates, probably due to lower care compared to the South region.